Ogier of Locedio in praise of god's holy mother : on our lord's words to his disciples at the last supper - Oglerius de Locedio ca. um 1130/40-1214 (Cistercian publications, 2006)
In praise of God's Holy Mother -- On our Lord's words to his disciples at the Last Supper
Umschlagtitel: Ogier of Locedio: Homilies
Keywords: Oglerius -- de Locedio -- ca. um 1130/40-1214; Maria -- von Nazaret, Biblische Person; Verehrung; Homilie; Mary / Sermons; Catholic Church / Sermons; Last Supper / Sermons; Sermons, Medieval; Sermons, Latin / Translated into English